Bunyi Gamelan Angklung Dalam Upacara Pitra Yadnya Di Kota Mataram (Ditinjau Dari Perspektif Sosiologi) - Ni Luh Eka Yuli Anggreni (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2021)
Some Hindu communities in the city of Mataram know that Gamelan Angklung is only used and serves to accompany the Pitra Yadnya ceremony or cremation because the sound produced by the tone or blade on the Gamelan Angklung has an impression that creates a sense of emotion and an atmosphere of sadness, then the sound of gending The sound produced from the angklung gamelan instrument is considered to sound always the same or monotonous between one type of gending and another when accompanying the Pitra Yadnya ceremony procession. From the background above, there are several problems that are studied, including: 1) What is the perception of the people in the West Karang Medain Region towards the sound of gamelan angklung in the Pitra Yadnya ceremony in Mataram City, 2) What is the essence of the sound of gamelan angklung in the Pitra Yadnya ceremony in the City of Mataram is viewed from a sociological perspective. This study uses a qualitative research method with a phenomenological approach. The problems studied used two theories, namely the theory of taste, and the theory of symbolic interactionism. The results of this study are as follows: People's perception of the West Karang Medain region to the sound of the angklung gamelan in the Pitra Yadnya ceremony in Mataram City, namely: 1). In terms of context of use, 2). In terms of the type of percussion, 3). In terms of how to enjoy it. The essence of the sound of the angklung gamelan in the Pitra Yadnya ceremony in Mataram City is viewed from a sociological perspective, including that: 1). The sound of the angklung gamelan in the Pitra Yadnya ceremony is used to accompany the ceremony and as a medium of information about the existence of a ceremonial procession or a natural means of social communication. 2). The sound of gamelan angklung indirectly and scientifically as a means of interaction to establish togetherness, connect friendship and brotherhood, generate social emotions, generate atmosphere and feeling, and learn social ethics. 3). The sound of gamelan angklung as a means of creating harmonization of life, be it with God, humans with humans, or humans with the universe.